Screening of breast cancer in higher-risk Taiwanese women using contrast-enhanced mammography - Chen-Pin Chou; Yu-Ting Hong; Yun Lin; Pei-Ying Lin (Heliyon)
Background: To assess the diagnostic performance of contrast-enhanced mammography (CEM) in screening higher-risk Taiwanese women for breast cancer. Methods: We conducted a prospective study at a Taiwanese medical center from 2019 to 2021. The study compared imaging techniques for breast cancer screening in women with a personal history of precancer or cancer, or a family history (first-degree relatives). The study included breast ultrasound (US) and the CEM combo, which consists of digital mammography (DM), digital breast tomosynthesis (DBT), and CEM. Diagnostic accuracy was compared using the receiver operating characteristic (ROC) curve. Results: The study included 308 women, average age 52.1, with 86 % having familial breast cancer history and 14 % personal breast cancer or pre-cancerous histories. Approximately 19.5 % had lesions rated BI-RADS 4 or 5. Biopsies were performed on 56 women based on lesions detected by the CEM combo. Additionally, 60 biopsies were due to abnormalities found via DM or DBT (n = 20) or US (n = 40). Breast cancer was confirmed in 8 women post-biopsy. The CEM combo showed a sensitivity of 87.5 %, significantly higher than DM (50 %), DBT (50 %), and US (25 %). The ROC curve area for CEM was 0.85, outperforming DM (0.65), DBT (0.63), and US (0.55), with all comparisons statistically significant (p < 0.05). Lesions detected solely by DM, DBT, or US did not yield any cancer cases. Conclusions: CEM effectively detects breast cancer in higher-risk Taiwanese women, but further research is needed to refine biopsy recommendations.